Tannic Acid Coating Augments Glioblastoma Cellular Uptake of Magnetic Nanoparticles with Antioxidant Effects - Świętek, Małgorzata; Ma, Yunn-Hwa; Wu, Nian-Ping; Paruzel, Aleksandra; Tokarz, Waldemar; Horák, Daniel (Nanomaterials (Basel, Switzerland), 2022)
Coating of nanoparticles with gallates renders them antioxidant and enhances cellular internalization. In this study, (amino)silica magnetic particles modified with tannic acid (TA) and optionally with chitosan (CS) were developed, and their physicochemical properties and antioxidant activity were evaluated. The results demonstrated that the TA-modified aminosilica-coated particles, as well as the silica-coated particles with a double TA layer, exhibited high antioxidant activity, whereas the silica-coated particles with no or only a single TA layer were well-internalized by LN-229 cells. In addition, a magnet placed under the culture plates greatly increased the cellular uptake of all TA-coated magnetic nanoparticles. The coating thus had a considerable impact on nanoparticle-cell interactions and particle internalization. The TA-coated magnetic nanoparticles have great potential as intracellular carriers with preserved antioxidant activity.
Keywords: tannic acid; cellular uptake; antioxidant activity; magnetic nanoparticles